Separating religion from cult: An analysis of cult-like organizations - Wheeler, Alisha (MacEwan University Student eJournal, 2020)
This paper explores the term "cult" and all of the connotations that are attached to it. This paper aims to separate the term cult from religious and spiritual assumptions while positing that the term is an umbrella term for various organizations, with cult-like traits, many of which operate in the corporate environment.